Building without Pillars: Nigeria and the Quagmire of Nation Building, 1966-1999 - Ugbede Joseph, Ineke (Kashere Journal of Humanities, Management and Social Sciences, 2022)
This paper adopts the historical and comparative approach. It depends significantly on the use of the primary and secondary sources. The paper explores the various institutional attempts at nation building in Nigeria since 1960. The basic aim of the paper is to discuss the principal factors that had defied the various governmental attempts at building a united Nigeria. The paper argues that, the various attempts at nation building particularly during the long years of military rule recorded only momentary success due to certain structural pitfalls. It further argues that some of the critical pillars that could have sustained the drive for the evolution of a stronger nation are yet to be prioritized as agents of nation building by the various administrations in the post-military era. The paper submits that for a meaningful evolution of a core sense of belonging to emerge among the various groups in Nigeria, certain pillars like the Military, Education, Language, and Security cannot be compromised. Thus, unless the aforementioned are given a core Nigerian colouration, Nation Building progresses in Nigeria will be a replica of a buildingwithout pillars.